2004
DOI: 10.1007/s00414-004-0447-2
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of carrion in the marine environment in British Columbia, Canada

Abstract: Decomposition of carrion in the marine environment is not well understood. This research involved the decomposition of pig carcasses in Howe Sound in British Columbia. Freshly killed pigs were submerged at two depths, 7.6 m and 15.2 m. The carcasses were tethered so that they could float or sink, but not drift away. Observations were made from May until October. Decomposition was more greatly influenced by sediment type of the sea floor and whether the carcass remained floating, than by depth. Decomposition st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 12 publications
(30 reference statements)
4
96
4
Order By: Relevance
“…To date, there have been no chemical studies of adipocere formation in water temperatures which approached zero and therefore further studies are required to confirm this finding. This study also demonstrated that adipocere can form in as little as 30 days in a cool water environment, which is comparable to the observational findings reported by Kahana et al [1] in seawater ( ~38 days) and Anderson and Hobischak [24] in freshwater (~9-35 days).…”
Section: Drift Spectroscopysupporting
confidence: 91%
See 1 more Smart Citation
“…To date, there have been no chemical studies of adipocere formation in water temperatures which approached zero and therefore further studies are required to confirm this finding. This study also demonstrated that adipocere can form in as little as 30 days in a cool water environment, which is comparable to the observational findings reported by Kahana et al [1] in seawater ( ~38 days) and Anderson and Hobischak [24] in freshwater (~9-35 days).…”
Section: Drift Spectroscopysupporting
confidence: 91%
“…Hobischak [24] also saw minimal variation in the degree of decomposition between carcasses submerged at 7.6m and 15m in seawater. However, they did observe greater differences between carcasses which floated versus those that remained in contact with the sea floor.…”
Section: Drift Spectroscopymentioning
confidence: 93%
“…Many species participate in the insect colonization of the carcass, triggering a process of succession; if the succession pattern is constant and know, it can be highly informative (Mise et al 2007). Thus, the study of insects associated with dead bodies may assist in solving crimes and their surrounding circumstances (sMith 1986;Catts & haskel 1990;anDerson & hobisChak 2004).…”
Section: _____________________________________mentioning
confidence: 99%
“…The main characteristics for identification include size, median area and chorionic sculpture pattern [16]. Blow fly eggs have been used to determine time of death in the early postmortem interval [17], when precise identification is very important. Larva stage: The lava is creamy and muscoid shaped.…”
Section: Fig 1-lateral Views Of Medically Important Blow Fly Speciesmentioning
confidence: 99%